Analisis Implementasi Prinsip Ekonomi Syariah dalam Kewirausahaan: Studi Kasus Pada UD Moroseneng Trowulan Mojokerto - Anwar, Ahmad Alif (Yayasan Rahmat Islamiyah, 2024)
This research aims to analyze the implementation of sharia economic principles in entrepreneurial activities at UD Moroseneng, a trading business located in Trowulan, Mojokerto. The research method used is qualitative with a case study approach, where data is obtained through in-depth interviews, observation and document analysis. The research results show that UD Moroseneng applies three sharia economic principles, including honesty, transparency and fairness in its business operations. Financial management is carried out without usury, with a fair profit sharing system between business owners and employees. Apart from that, this business also pays attention to aspects of sustainability and social care in its operations, which are in line with sharia values. However, there are several challenges in fully implementing sharia economics, such as limited knowledge and in-depth understanding among business actors. This research concludes that the implementation of sharia economics at UD Moroseneng contributes positively to business sustainability and growth, although improvements are still needed in a more comprehensive understanding and implementation of sharia principles.